Cell cholesterol modulates metalloproteinase-dependent shedding of low-density lipoprotein receptor-related protein-1 (LRP-1) and clearance function. - Selvais, C; D'Auria, L; Tyteca, D; Perrot, G; Lemoine, P; Troeberg, L; Dedieu, S; Noël, A; Nagase, H; Henriet, P; Courtoy, P; Marbaix, E; et al. (2011)
Low-density lipoprotein receptor-related protein-1 (LRP-1) is a plasma membrane scavenger and signaling receptor, composed of a large ligand-binding subunit (515-kDa α-chain) linked to a shorter transmembrane subunit (85-kDa β-chain). LRP-1 cell-surface level and function are controlled by proteolytic shedding of its ectodomain. Here, we identified ectodomain sheddases in human HT1080 cells and demonstrated regulation of the cleavage by cholesterol by comparing the classical fibroblastoid type with a spontaneous epithelioid variant, enriched ∼ 2-fold in cholesterol. Two membrane-associated metalloproteinases were involved in LRP-1 shedding: a disintegrin and metalloproteinase-12 (ADAM-12) and membrane-type 1 matrix metalloproteinase (MT1-MMP). Although both variants expressed similar levels of LRP-1, ADAM-12, MT1-MMP, and specific tissue inhibitor of metalloproteinases-2 (TIMP-2), LRP-1 shedding from epithelioid cells was ∼4-fold lower than from fibroblastoid cells. Release of the ectodomain was triggered by cholesterol depletion in epithelioid cells and impaired by cholesterol overload in fibroblastoid cells. Modulation of LRP-1 shedding on clearance was reflected by accumulation of gelatinases (MMP-2 and MMP-9) in the medium. We conclude that cholesterol exerts an important control on LRP-1 levels and function at the plasma membrane by modulating shedding of its ectodomain, and therefore represents a novel regulator of extracellular proteolytic activities.